Method for producing polyester film using chemical recycling, and polyester film

By using chemically recycled polyethylene terephthalate resin in the production of polyester films and performing melt-mixed treatment, the problem of unstable film characteristics caused by fluctuations in the addition amount of recovered polyester resin is solved, and the film characteristics are achieved Stable production improves the environmental load reduction effect.

CN119487103APending Publication Date: 2025-02-18TOYOBO CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380049293.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-13
Filing Date
2023-07-05
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

During the manufacturing process of the polyester film, due to the fluctuation of the addition amount of the recovered polyester resin, various characteristics of the film are difficult to maintain stability, especially when the production volume fluctuates, it is difficult to ensure the quality of the film.

Method used

Polyethylene terephthalate resin that is not used is recycled and the polyethylene terephthalate resin recovered during the manufacturing process is recycled by using chemically recycled polyethylene terephthalate resin and during the manufacturing process The resin is melted and mixed and formed into a film shape. This method ensures that the proportion of the polyester resin recovered is between 5 and 50 mass %, and the intrinsic viscosity and acid value of the resin are controlled by adding an aluminum compound and a phosphorus compound as a catalyst.

Benefits of technology

It is achieved that even if the amount of the recovered polyester film is added fluctuated, the various characteristics of the film will not change greatly, ensuring the stable quality of the film, and thus improving the effect of reducing environmental load.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005204089810000061
    Figure BDA0005204089810000061
  • Figure BDA0005204089810000071
    Figure BDA0005204089810000071
  • Figure BDA0005204089810000082
    Figure BDA0005204089810000082
Patent Text Reader

Abstract

A polyester film obtained by melting and molding a polyester resin, the polyester film being obtained by polycondensing a starting material containing bis (2-hydroxyethyl) terephthalate obtained by decomposing the polyester resin using an aluminum compound and a phosphorus compound as catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a polyester film using a polyester resin obtained by polycondensation using bis(2-hydroxyethyl)terephthalate obtained by chemical recycling, and the obtained polyester film. Background Art

[0002] Polyester films are widely used as packaging and industrial parts because they are excellent in mechanical strength, chemical stability, heat resistance, and moisture resistance, and because they have improved transparency and can be stably supplied at low prices.

[0003] The most common polyester film is polyethylene terephthalate, which is a polycondensate of terephthalic acid and ethylene glycol. Terephthalic acid and ethylene glycol are produced from petroleum, which is a fossil fuel. In recent years, in order to reduce carbon dioxide emissions and other environmental loads, the recycling and reuse of products from fossil fuels has been developed. In terms of polyester, not only mechanical recycling of crushing products and remelting them into shapes, but also chemical recycling of decomposing polyester to the monomer level and re-condensing them as raw materials is being put into practical use (for example, Patent Document 1).

[0004] In the case of polyester films, in order to reduce environmental load, research is also underway to use polyethylene terephthalate obtained by chemically recycling PET bottles for beverages, polyester fibers for clothing, etc. In such films that address environmental loads, in many cases, the proportion of chemically recycled raw materials is made to be at least a certain amount to ensure the extent to which environmental loads are addressed.

[0005] On the other hand, in the manufacture of polyester film, not all the polyester resins put into the manufacture will become films due to the parts clamped by the clamps of the tenter during transverse stretching, the films that do not meet the requirements that are shipped until the manufacturing conditions are stabilized and the products can be produced, etc. These recycled polyester resins obtained from the film manufacturing process are sometimes reused as raw materials in the film manufacturing, but once melted and placed in a high-temperature environment, they will decompose, causing a decrease in molecular weight, an increase in terminal carboxyl groups, etc. In order to stabilize the quality of the film using such recycled polyester resin, it is preferred to always add a certain amount of recycled polyester resin, but in the manufacture of the film, a certain amount of recycled polyester resin is not always generated, and a certain amount is not always produced. Therefore, among the recycled polyester resins, in most cases, those collected from multiple production lines, including products of different brands, are collected together as recycled polyester resins for reuse.

[0006] However, in the film that copes with the environmental load, due to the restrictions as mentioned above, it is necessary to prevent non-chemically recycled raw materials from being mixed into the recycled polyester resin at will, and sometimes it is difficult to ensure a certain amount of recycled polyester resin. In the case where the production volume fluctuates in a short period of time instead of being stably produced, it is difficult to avoid fluctuations in the amount of recycled polyester resin added.

[0007] Therefore, in films made of chemically recycled polyethylene terephthalate, it has become increasingly required that various properties of the obtained films do not change significantly even if the amount of recycled polyester film added fluctuates. Prior art literature Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2004-175912 Summary of the invention Problems to be solved by the invention

[0009] The present invention has been accomplished against the background of the above-mentioned problems in the prior art. That is, the purpose of the present invention is to provide a polyester film and a method for producing the same, wherein the various properties of the obtained film do not change significantly even if the amount of recycled polyester film added fluctuates in the film made of chemically recycled polyethylene terephthalate. Means for solving problems

[0010] The present invention includes the following configurations. [Item 1] A polyester film comprising a chemically recycled polyethylene terephthalate resin obtained by polycondensing a raw material containing bis(2-hydroxyethyl) terephthalate obtained by decomposing a polyester resin using an aluminum compound and a phosphorus compound as a catalyst. [Item 2] The polyester film according to Item 1, wherein the ratio of the raw material containing bis(2-hydroxyethyl) terephthalate is 50% by mass or more. [Item 3] The polyester film according to Item 1 or 2, wherein the polyester resin comprises a recycled polyester resin obtained in a film production step. [Item 4] The polyester film according to Item 3, wherein the ratio of the recovered polyester resin in the total polyester resin constituting the polyester film is 5 to 50% by mass. [Item 5] The polyester film according to Item 1 or 3, wherein the intrinsic viscosity of the polyester resin constituting the polyester film is 0.52 to 0.73 dL / g. [Item 6] The polyester film according to Item 1 or 3, wherein the acid value of the polyester resin constituting the polyester film is 5 to 80 dL / g. [Item 7] A method for producing a polyester film, characterized in that it comprises the following steps: producing a polyester film using a chemically recycled polyethylene terephthalate resin, wherein the chemically recycled polyethylene terephthalate resin is obtained by polycondensing a raw material containing bis(2-hydroxyethyl) terephthalate obtained by decomposing a polyester resin; Unused chemically recycled polyethylene terephthalate resin obtained by polycondensing the raw material containing bis(2-hydroxyethyl) terephthalate and polyethylene terephthalate resin obtained by recovering a melt-formed product discharged from the step of manufacturing the polyester film are melt-mixed and formed into a film. [Item 8] The method for producing a polyester film according to Item 7, wherein the recycled polyethylene terephthalate resin is 5 to 50% by mass relative to the total amount of the unused chemically recycled polyethylene terephthalate resin and the recycled polyethylene terephthalate resin. [Item 9] A method for producing a polyester film according to Item 7 or 8, wherein, in the chemically recycled polyethylene terephthalate resin obtained by polycondensing the raw material containing bis(2-hydroxyethyl) terephthalate, the proportion of bis(2-hydroxyethyl) terephthalate obtained by decomposing the polyester resin is 50% by mass or more relative to the total amount of bis(2-hydroxyethyl) terephthalate used as a raw material for the polycondensation resin. [Item 10] A method for producing a polyester film according to Item 7 or 8, wherein the chemically recycled polyethylene terephthalate resin obtained by polycondensing bis(2-hydroxyethyl) terephthalate obtained by decomposing the polyester resin contains an aluminum compound and a phosphorus compound as a catalyst. [Item 11] The method for producing a polyester film according to Item 7 or 8, wherein the difference between the intrinsic viscosity of the unused chemically recycled polyethylene terephthalate resin and the intrinsic viscosity of the recovered polyethylene terephthalate resin is 0.1 dL / g or less. [Item 12] The method for producing a polyester film according to Item 7 or 8, wherein the ratio of the intrinsic viscosity of the unused chemically recycled polyethylene terephthalate resin to the intrinsic viscosity of the recovered polyethylene terephthalate resin is 0.85 to 1. [Item 13] The method for producing a polyester film according to Item 7 or 8, wherein the difference between the acid value of the unused chemically recycled polyethylene terephthalate resin and the acid value of the recovered polyethylene terephthalate resin is 22 eq / ton or less. Effects of the Invention

[0011] According to the present invention, a polyester film can be obtained, wherein the polyester film is a film made of chemically recycled polyethylene terephthalate, and the various properties of the obtained film will not change significantly even if the amount of recycled polyester film added fluctuates. Even if the production volume fluctuates, a film with stable quality can be supplied, thereby further improving the effect of reducing the environmental load. DETAILED DESCRIPTION

[0012] In the present invention, polyethylene terephthalate obtained by polymerization using bis(2-hydroxyethyl)terephthalate obtained by chemical recycling is melted and formed to form a polyester film. It should be noted that, bis(2-hydroxyethyl)terephthalate may be abbreviated as BHET, and bis(2-hydroxyethyl)terephthalate obtained by chemical recycling may be abbreviated as chemically recycled BHET or CR-BHET.

[0013] Chemically recycled BHET is obtained by heating and depolymerizing polyethylene terephthalate in the presence of ethylene glycol. Hereinafter, polyethylene terephthalate is sometimes referred to as PET. As for PET raw materials, it is preferably an article that has been used in some form. As examples, there can be cited PET bottles, containers such as pallets, fibers or products recovered from the streets, discarded products before making products in manufacturing, products that have not been shipped to the market as B-grade products, ears held during film stretching, end materials for slitting, and molded products returned due to complaints, etc. As for these PET raw materials, terephthalic acid and ethylene glycol can come from petroleum, or can come from biomass. In addition, it can also be a molded product that is mechanically recycled. In addition, it can also be a mixture of these PETs.

[0014] These PET raw materials are generally used in the depolymerization process after being crushed, cleaned, and freed of foreign matter.

[0015] The chemically recycled BHET may contain a linear dimer or a multimer thereof or more, and may also contain mono-2-hydroxyethyl terephthalate, terephthalic acid, and ethylene glycol.

[0016] The total of the acid value and hydroxyl value of chemical recycling BHET is preferably 6500 eq / ton or more, preferably 7000 eq / ton or more, and more preferably 7500 eq / ton or more. The upper limit is preferably 9500 eq / ton, more preferably 9000 eq / ton, and more preferably 8500 eq / ton. By setting it to the above range, productivity can be ensured while maintaining sufficient purity.

[0017] Chemically recycled BHET may contain dicarboxylic acid components other than terephthalic acid components and diol components other than ethylene glycol. Examples of dicarboxylic acid components other than terephthalic acid components include naphthalene dicarboxylic acid and isophthalic acid, and examples of diol components other than ethylene glycol include diethylene glycol, neopentyl glycol, cyclohexanedimethanol, trimethylene glycol, tetramethylene glycol, ethylene glycol or propylene glycol adducts of bisphenol A, and ethylene glycol or propylene glycol adducts of bisphenol S.

[0018] Regarding the amount of dicarboxylic acid components other than terephthalic acid components and the amount of glycol components other than ethylene glycol, when the terephthalic acid components and the ethylene glycol components are set to 100 mol%, they are preferably 2 mol% or less, more preferably 1.5 mol% or less, further preferably 1.0 mol% or less, particularly preferably 0.7 mol% or less, and most preferably 0.5 mol% or less. In addition, as described above, chemically recycled BHET is preferably obtained by depolymerizing PET containing recycled products from the market. The recycled PET from the market sometimes has components other than PET added to adjust crystallinity, physical properties, etc., but it is not preferred from the cost point of view to select only pure PET from the recycled products or purify BHET to the extent that components other than terephthalic acid and ethylene glycol cannot be detected. Therefore, the amount of dicarboxylic acid components other than terephthalic acid components and the amount of glycol components other than ethylene glycol are preferably present at 0.01 mol% or more, and more preferably at 0.05 mol% or more.

[0019] For chemically recycled BHET, a polycondensation catalyst is added, and polycondensation is carried out by heating under reduced pressure to prepare a chemically recycled polyethylene terephthalate resin. At this time, the lower limit of the amount of chemically recycled BHET is preferably 50% by mass, more preferably 60% by mass, further preferably 70% by mass, particularly preferably 80% by mass, and most preferably 90% by mass, relative to the total amount of BHET used. By setting it to the above, environmental adaptability can be improved.

[0020] In addition, in the chemically recycled polyethylene terephthalate resin, copolymer components other than chemically recycled BHET can be added. Representative copolymerizable dicarboxylic acid components and diol components are the same as the components listed as components that can be contained in the above-mentioned chemically recycled BHET. Regarding the amount of dicarboxylic acid components other than terephthalic acid components and the amount of diol components other than ethylene glycol, when the terephthalic acid component and the ethylene glycol component are set to 100 mol%, they are independently preferably 20 mol% or less, more preferably 15 mol% or less, further preferably 10 mol% or less, particularly preferably 7 mol% or less, and most preferably 5 mol% or less. It should be noted that this amount also includes those from other than chemically recycled BHET.

[0021] Hereinafter, chemically recycled polyethylene terephthalate may be referred to as chemically recycled PET or CR-PET.

[0022] As a catalyst for polycondensation using chemically recycled BHET, any catalyst commonly used can be used without limitation. For example, antimony compounds, titanium compounds, germanium compounds, composite catalysts of aluminum compounds and phosphorus compounds, etc. can be cited. Among them, antimony compounds and aluminum compounds are preferred because the resulting PET has high thermal stability. As a representative example of antimony compounds, antimony trioxide can be cited.

[0023] Regarding the amount of antimony compound added, the lower limit is preferably 50 mass ppm, more preferably 80 mass ppm, and further preferably 100 mass ppm, based on the content of antimony element in the obtained recycled PET. By setting it to above, an economic polymerization rate can be ensured. The upper limit of the content of antimony element is preferably 330 mass ppm, more preferably 300 mass ppm, further preferably 270 mass ppm, particularly preferably 250 mass ppm, and most preferably 230 mass ppm. By setting it to below the above, the decomposition of the recycled resin can be suppressed.

[0024] Examples of the composite catalyst of an aluminum compound and a phosphorus compound include the following catalysts. (Aluminum compounds) The aluminum compound is not limited as long as it is an aluminum compound that is soluble in a solvent, and any known aluminum compound can be used without limitation, among which at least one selected from carboxylates, inorganic acid salts, and chelate compounds is preferred. Among them, at least one selected from aluminum acetate, basic aluminum acetate, aluminum chloride, aluminum hydroxide, basic aluminum chloride, and aluminum acetylacetonate is more preferred, at least one selected from aluminum acetate, basic aluminum acetate, aluminum chloride, aluminum hydroxide, basic aluminum chloride, and aluminum acetylacetonate is further preferred, at least one selected from aluminum acetate and basic aluminum acetate is particularly preferred, and basic aluminum acetate is most preferred.

[0025] The amount of aluminum compound added is preferably 5 to 50 mass ppm, more preferably 7 to 40 mass ppm, further preferably 10 to 30 mass ppm, and particularly preferably 15 to 25 mass ppm, based on the aluminum content in chemically recycled PET. When the aluminum content is less than 5 mass ppm, there is a concern that the polymerization activity cannot be fully exerted. On the other hand, when the aluminum content is greater than 50 mass ppm, there is a concern that the amount of aluminum-based foreign matter increases.

[0026] In addition, when cost is emphasized, the content of aluminum in chemically recycled PET is preferably 9 to 20 mass ppm, more preferably 9 to 19 mass ppm, further preferably 10 to 17 mass ppm, and particularly preferably 12 to 17 mass ppm. When the aluminum content is less than 9 mass ppm, there is a concern that the polymerization activity cannot be fully exerted. On the other hand, when it is more than 20 mass ppm, there is a concern that the amount of aluminum-based foreign matter increases due to the relationship with the content of phosphorus described later, and the cost of the catalyst increases.

[0027] (Phosphorus compounds) The phosphorus compound is not particularly limited, but phosphonic acid compounds and phosphinic acid compounds are preferred because they have a large effect of improving the catalytic activity. Among them, phosphonic acid compounds are more preferred because they have a particularly large effect of improving the catalytic activity.

[0028] Among the above-mentioned phosphorus compounds, phosphorus compounds having a phosphorus element and a phenol structure in the same molecule are preferred. There are no particular limitations on the phosphorus compound as long as it has a phosphorus element and a phenol structure in the same molecule, but when one or more compounds selected from phosphonic acid compounds having a phosphorus element and a phenol structure in the same molecule and phosphinic acid compounds having a phosphorus element and a phenol structure in the same molecule are used, the effect of improving the catalytic activity is large, so it is preferred, and when one or more phosphonic acid compounds having a phosphorus element and a phenol structure in the same molecule are used, the effect of improving the catalytic activity is very large, so it is more preferred.

[0029] In addition, examples of phosphorus compounds having a phosphorus element and a phenol structure in the same molecule include P(=O)R 1 (OR 2 )(OR 3 ) or P(=O)R 1 R 4 (OR 2 ) represented by the compound, etc. 1 R represents a hydrocarbon group having 1 to 50 carbon atoms containing a phenol portion, or a hydrocarbon group having 1 to 50 carbon atoms containing a substituent such as a hydroxyl group, a halogen group, an alkoxy group, or an amino group and a phenol structure. 4 R represents hydrogen, a hydrocarbon group having 1 to 50 carbon atoms, or a hydrocarbon group having 1 to 50 carbon atoms which has a substituent such as a hydroxyl group, a halogen group, an alkoxy group, or an amino group. 2 , R 3 R each independently represents hydrogen, a hydrocarbon group having 1 to 50 carbon atoms, or a hydrocarbon group having 1 to 50 carbon atoms and containing a substituent such as a hydroxyl group or an alkoxy group. The hydrocarbon group may contain a branched structure, an alicyclic structure such as a cyclohexyl group, or an aromatic ring structure such as a phenyl group or a naphthyl group. 2 With R 4 The ends of the molecule may be bonded to each other.

[0030] Examples of the phosphorus compound having a phosphorus element and a phenol structure in the same molecule include p-hydroxyphenylphosphonic acid, dimethyl p-hydroxyphenylphosphonate, diethyl p-hydroxyphenylphosphonate, diphenyl p-hydroxyphenylphosphonate, bis(p-hydroxyphenyl)phosphinic acid, methyl bis(p-hydroxyphenyl)phosphinic acid, phenyl bis(p-hydroxyphenyl)phosphinic acid, p-hydroxyphenylphosphinic acid, methyl p-hydroxyphenylphosphinic acid, and phenyl p-hydroxyphenylphosphinic acid.

[0031] As the phosphorus compound having a phosphorus element and a phenol structure in the same molecule, in addition to the above examples, there can be mentioned: a phosphorus compound having a phosphorus element and a hindered phenol structure (a phenol structure having a tertiary carbon alkyl group (preferably a tertiary carbon alkyl group such as a tertiary carbon alkyl group such as a tertiary butyl group, 1,1,2-trimethylpropyl (thexyl) group at the benzyl position; a neopentyl group, etc.) bonded to one or two ortho positions of a hydroxyl group, etc.) in the same molecule, preferably a phosphorus compound having a phosphorus element and a structure of the following (chemical formula A) in the same molecule, and more preferably 3,5-di-tert-butyl-4-hydroxybenzyl dialkylphosphonate shown in the following (chemical formula B). It should be noted that as the phosphorus compound used in the production of the polyester resin (B), 3,5-di-tert-butyl-4-hydroxybenzyl dialkylphosphonate shown in the following (chemical formula B) is preferred, but in addition, a modified product of 3,5-di-tert-butyl-4-hydroxybenzyl dialkylphosphonate may be contained. The details of the modified product will be described later.

[0032]

[0033] (In (Chemical Formula A), * represents a bonding bond.)

[0034]

[0035] ((Chemical Formula B) where X 1 , X 2 represents hydrogen or an alkyl group having 1 to 4 carbon atoms.) In this specification, a polyester resin in which at least one hindered phenol structure can be detected by a P-NMR measurement method of a solution dissolved in a hexafluoroisopropanol-based solvent is referred to as "having a hindered phenol structure". That is, chemically recycled PET is preferably a polyester resin produced using a phosphorus compound having a phosphorus element and a hindered phenol structure in the same molecule as a polymerization catalyst. The method for detecting the hindered phenol structure in PET (P-NMR measurement method) will be described later.

[0036] In the above (chemical formula B), X 1 , X 2All of them are preferably alkyl groups having 1 to 4 carbon atoms, and more preferably alkyl groups having 1 to 2 carbon atoms. In particular, an ethyl ester having 2 carbon atoms is preferred because it is commercially available as Irganox 1222 (manufactured by BASF Corporation) and is easily available.

[0037] The phosphorus compound is preferably used by heat treatment in a solvent. It should be noted that the details of the heat treatment will be described later. When the phosphorus compound represented by the above (chemical formula B), i.e., 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester, is used as the phosphorus compound, during the above heat treatment, a part of the phosphorus compound represented by (chemical formula B), i.e., 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester, undergoes structural changes. For example, the tert-butyl group is separated, the ethyl ester group is hydrolyzed, and converted into a hydroxyethyl ester exchange structure (ester exchange structure with ethylene glycol), etc. occurs. Therefore, in the present invention, as a phosphorus compound, in addition to the 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester represented by (chemical formula B), a phosphorus compound with a changed structure is also included. It should be noted that the separation of the tert-butyl group occurs significantly at high temperatures in the polymerization process.

[0038] Nine types of phosphorus compounds in which a part of diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate has undergone structural changes are shown below. The amount of each phosphorus compound in which the structure has undergone structural changes in the diol solution can be quantified by a P-NMR measurement method.

[0039]

[0040] Therefore, as the phosphorus compound in the present invention, in addition to 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester, 9 kinds of modified substances of 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester represented by the above chemical formula may be included.

[0041] When Irganox 1222 is used as the phosphorus compound, the polyester resin contains 9 types of phosphorus compound residues shown in Table 1 below. When at least one of the 9 types of hindered phenol structures shown in Table 1 is detected by the P-NMR measurement method, the polyester resin (B) can be considered to be a polyester resin produced using a phosphorus compound having a phosphorus element and a hindered phenol structure in the same molecule as a polymerization catalyst. By using a phosphorus compound having a hindered phenol structure, sufficient polymerization activity can be exerted while suppressing the catalyst cost.

[0042] [Table 1]

[0043] In the present invention, it is preferred that at least one of the above Chemical Formulas 1, 4 and 7 is contained.

[0044] The phosphorus content in chemically recycled PET is preferably 5 to 1000 mass ppm, more preferably 10 to 500 mass ppm, further preferably 15 to 200 mass ppm, particularly preferably 20 to 100 mass ppm, and most preferably 30 to 50 mass ppm. When the phosphorus content is less than 5 mass ppm, there is a concern that the polymerization activity decreases and the amount of aluminum-based foreign matter increases. On the other hand, when it is greater than 1000 mass ppm, on the contrary, there is a concern that the polymerization activity decreases and there is a concern that the amount of phosphorus compound added increases and the catalyst cost increases.

[0045] When cost is given more importance, the phosphorus content in chemically recycled PET is preferably 13 to 31 mass ppm, more preferably 15 to 29 mass ppm, and even more preferably 16 to 28 mass ppm. When the phosphorus content is less than 13 mass ppm, there is a concern that the polymerization activity decreases and the amount of aluminum-based foreign matter increases. On the other hand, when it is greater than 31 mass ppm, on the contrary, there is a concern that the polymerization activity decreases, the amount of phosphorus compound added increases, and the catalyst cost increases.

[0046] The molar ratio of phosphorus to aluminum in chemically recycled PET is preferably 1.00 to 5.00, more preferably 1.10 to 4.00, further preferably 1.20 to 3.50, and particularly preferably 1.25 to 3.00. As described above, the aluminum and phosphorus in chemically recycled PET are derived from the aluminum compound and phosphorus compound used as a polymerization catalyst, respectively. By using these aluminum compounds and phosphorus compounds in a specific ratio, a complex having catalytic activity can be functionally formed in the polymerization system, and sufficient polymerization activity can be exerted. In addition, compared with polyester resins produced using catalysts such as antimony catalysts, the cost of the catalyst in the resin produced using a polymerization catalyst containing an aluminum compound and a phosphorus compound is high (the production cost is high), but by using aluminum compounds and phosphorus compounds in a specific ratio, the cost of the catalyst can be controlled while exerting sufficient polymerization activity. When the residual molar ratio of phosphorus to aluminum is less than 1.00, there is a concern that thermal stability and thermal oxidation stability are reduced, and there is a concern that the amount of aluminum-based foreign matter increases. On the other hand, when the residual molar ratio of phosphorus element to aluminum element exceeds 5.00, the amount of the phosphorus compound added becomes too large, so there is a concern that the catalyst cost may increase.

[0047] When cost is given more importance, the residual molar ratio of phosphorus element to aluminum element is preferably 1.32 to 1.80, and more preferably 1.38 to 1.68.

[0048] Chemically recycled PET is melted, mixed, and formed into a film. In the formation of the film, not all of the resin input is shipped as a product. There are process recycles such as cut ends, slitting end materials, and films until stable production. The recycles from these processes may not be discarded but recycled as raw material resins for reasons such as environmental protection based on resource saving and cost reduction. In particular, in the case of a PET film stretched in the width direction by a tenter, a large amount of process recycles are generated because the part clamped by the tenter is not stretched.

[0049] In the present invention, such process recycle products are preferably mixed with unused chemically recycled PET and reused as raw materials for film manufacturing. In addition, there are films that cannot be shipped due to characteristics not meeting specifications or films that are returned due to complaints, etc., which are also preferably mixed with process recycle products and reused. Hereinafter, PET containing process recycle products is sometimes referred to as recycled PET, and unused chemically recycled PET is sometimes referred to as virgin PET. It should be noted that unused means that after PET is manufactured and made into pellets, it has not been re-melted and solidified.

[0050] Recycled PET may be directly fed into a film production facility after being pulverized, but in order to stabilize the amount fed and suppress segregation from virgin PET in the hopper, it is preferably pelletized by remelting.

[0051] In the present invention, in the production of the film, it is preferred to use, as the raw material PET, virgin PET of chemically recycled PET and recovered PET generated in the film production process of chemically recycled PET.

[0052] In the film manufacturing, the lower limit of the ratio of the recycled PET to the total raw material resin is preferably 5% by mass, more preferably 10% by mass, and further preferably 15% by mass. The upper limit of the recycled PET ratio is preferably 50% by mass, more preferably 40% by mass, and further preferably 35% by mass. By setting it to the above range, it is possible to achieve stable production and quality stability of the raw materials.

[0053] In the production of the film, the raw material PET used does not need to be all chemically recycled PET, and may contain PET obtained from terephthalic acid and ethylene glycol in the past. In particular, in the production of the film, when adding lubricant particles, resistivity adjusters, pigments, ultraviolet absorbers, etc., there are cases where they are mixed as a masterbatch, but it is not necessarily necessary to use chemically recycled PET for the PET used in the masterbatch, and economical production can be sought by sharing them with the raw materials for ordinary PET films.

[0054] In the production of the film, the raw material resin may not be entirely PET, and may contain copolyester or other resins depending on the application, etc. The specific copolyester or other resins will be described in the examples of application later. In this case, even if the resin recovered from the film production process contains a resin other than PET, it is considered to be recycled PET.

[0055] The lower limit of the ratio of the chemically recycled PET amount to the total resin constituting the film is preferably 20% by mass, more preferably 30% by mass, further preferably 50% by mass, particularly preferably 70% by mass, and most preferably 80% by mass. By setting the ratio to the above, environmental compatibility can be improved.

[0056] Such recycled PET has a lower molecular weight and an increased terminal carboxyl group content compared to virgin PET. As an index of molecular weight, it is preferred to use intrinsic viscosity, referred to as IV, and terminal carboxyl group content, referred to as AV, and cyclic trimer, referred to as CT. In order to reduce the quality variation between batches even when the amount of recycled PET added varies in each batch of production, it is preferred to set the difference in IV, AV, etc. between virgin PET and recycled PET to a specific range.

[0057] The lower limit of the IV difference between the original PET and the recycled PET is preferably 0.01 dL / g, and more preferably 0.02 dL / g, from a practical point of view. The upper limit of the IV difference between the original PET and the recycled PET is preferably 0.1 dL / g, more preferably 0.08 dL / g, further preferably 0.07 dL / g, particularly preferably 0.065 dL / g, and most preferably 0.06 dL / g.

[0058] The lower limit of the ratio of IV of recycled PET to IV of virgin PET, i.e., IV of recycled PET / IV of virgin PET, is preferably 0.85, more preferably 0.87, further preferably 0.88, particularly preferably 0.89, and most preferably 0.9. The upper limit of IV of recycled PET / IV of virgin PET is preferably 0.99, more preferably 0.98, from a practical point of view.

[0059] The AV difference between virgin PET and recycled PET is preferably 3 eq / ton, more preferably 4 eq / ton, and further preferably 5 eq / ton from a practical point of view. The upper limit of the AV difference between virgin PET and recycled PET is preferably 22 eq / ton, more preferably 20 eq / ton, further preferably 17 eq / ton, particularly preferably 15 eq / ton, and most preferably 13 eq / ton.

[0060] By setting the IV difference between virgin PET and recycled PET, the IV value of recycled PET / IV value of virgin PET, and the AV difference between virgin PET and recycled PET within the above range, the quality stability of the product can be ensured even when the amount of recycled PET added varies in each batch of production. It should be noted that, from a practical point of view, the above means that solid phase polymerization of recycled PET or remelting and dehydration polymerization under reduced pressure are not performed, or even if they are performed, strict management is not required, and there is no need to perform complicated means such as sorting recycled PET into different IVs and then selecting them together with the IV of virgin PET, and it can be performed by an economically simple method.

[0061] CT in PET is an equilibrium reaction, and its amount is roughly determined by the resin temperature. Therefore, when neither the original PET nor the recycled PET undergoes solid phase polymerization, the CT content is roughly the same. In this case, the upper limit of the difference in CT content between the original PET and the recycled PET is preferably 0.1% by mass, and more preferably 0.08% by mass.

[0062] On the other hand, when the virgin PET is subjected to solid phase polymerization, the CT content is reduced. In this case, the recycled PET can be subjected to solid phase polymerization, and the lower limit of the difference in CT content between the virgin PET and the recycled PET is preferably 0% by mass, more preferably 0.02% by mass, and further preferably 0.05% by mass. The upper limit of the difference in CT content between the virgin PET and the recycled PET is preferably 0.4% by mass, more preferably 0.3% by mass, further preferably 0.2% by mass, and particularly preferably 0.15% by mass.

[0063] In order to set the difference in IV, AV, and CT content between virgin PET and recycled PET to the above range, it is preferred that the IV, AV, and CT content of virgin PET be within a specific range.

[0064] The lower limit of IV of virgin PET is preferably 0.54 dL / g, more preferably 0.56 dL / g, further preferably 0.57 dL / g, and particularly preferably 0.58 dL / g. By setting the lower limit to the above, the mechanical properties of the obtained film can be ensured, and the difference in IV and AV between virgin PET and recycled PET can be easily reduced, thereby easily suppressing the fluctuation of mechanical properties and ensuring the stability of film production.

[0065] The upper limit of IV of the original PET is preferably 0.75 dL / g, more preferably 0.70 dL / g, further preferably 0.68 dL / g, particularly preferably 0.66 dL / g, and most preferably 0.65 dL / g. By setting it below the above, film-making stability can be ensured, and degradation of the recycled resin can be easily suppressed, and the difference in IV and AV between the original PET and the recycled PET can be easily reduced. In addition, when it is below 0.68 dL / g, only melt polymerization can be performed, which is advantageous in terms of economic efficiency.

[0066] From the perspective of productivity, the lower limit of AV of the original PET is preferably 1 eq / ton, more preferably 3 eq / ton, and further preferably 5 eq / ton. When PET is produced only by melt polymerization, the lower limit is preferably 10 eq / ton, and more preferably 15 eq / ton. When the AV is 10 eq / ton or more, only melt polymerization can be performed, which is advantageous in terms of economic efficiency.

[0067] The upper limit of AV of virgin PET is preferably 70 eq / ton, more preferably 60 eq / ton, further preferably 55 eq / ton, and particularly preferably 50 eq / ton. By setting the upper limit to the above or lower value, it is easy to suppress the degradation of the recycled resin.

[0068] From the perspective of productivity, the lower limit of the CT amount of the original PET is preferably 0.3% by mass, more preferably 0.5% by mass, further preferably 0.7% by mass, and particularly preferably 0.8% by mass. The upper limit of the CT amount of the original PET is preferably 1.1% by mass, more preferably 1.05% by mass, and further preferably 1% by mass. By setting it below the above, it can be produced. In the case of producing PET only by melt polymerization, the CT amount is about 0.9 to 1.0% by mass.

[0069] The lower limit of IV of recycled PET is preferably 0.5 dL / g, more preferably 0.51 dL / g, and further preferably 0.52 dL / g. By setting it to above, the mechanical properties of the obtained film can be ensured, and the difference in IV between the original PET and the recycled PET can be easily reduced, thereby easily suppressing the fluctuation of mechanical properties and ensuring the stability of film production.

[0070] The upper limit of IV of recycled PET is preferably 0.72 dL / g, more preferably 0.68 dL / g, further preferably 0.66 dL / g, particularly preferably 0.64 dL / g, and most preferably 0.63 dL / g. By setting it below the above, film forming stability can be ensured, and the difference in IV and AV between the original PET and the recycled PET can be easily reduced. In addition, when it is below the above, solid phase polymerization of the recycled PET does not need to be performed, or even if solid phase polymerization is performed, it can be performed in a short time, which is advantageous in terms of cost.

[0071] The lower limit of the AV of the recycled PET is preferably 3 eq / ton, more preferably 5 eq / ton, further preferably 10 eq / ton, particularly preferably 15 eq / ton, and most preferably 20 eq / ton. When the above is above, there is no need to perform solid phase polymerization on the recycled PET, or even if solid phase polymerization is performed, it can be performed in a short time, which is advantageous in terms of cost. The upper limit of the AV of the recycled PET is preferably 85 eq / ton, more preferably 80 eq / ton, further preferably 75 eq / ton, particularly preferably 70 eq / ton, and most preferably 65 eq / ton. By setting it to the above or below, the degradation of the resin when the recycled resin is added to produce the film can be suppressed.

[0072] The lower limit of the CT amount of the recycled PET is preferably 0.5% by mass, more preferably 0.7% by mass, and further preferably 0.8% by mass. The upper limit of the CT amount of the recycled PET is preferably 1.1% by mass, more preferably 1.05% by mass, and further preferably 1% by mass. When a film made of only melt-polymerized PET is used as the recycled PET, the CT amount is about 0.9 to 1.0% by mass.

[0073] In the whole raw material PET of the film, the lower limit of the proportion of recycled PET is preferably 5% by mass, more preferably 10% by mass, and further preferably 15% by mass. The upper limit of the proportion of recycled PET is preferably 50% by mass, more preferably 40% by mass, and further preferably 35% by mass. By setting it to the above range, stable production by recycling raw materials and quality stability of the obtained film can be ensured.

[0074] In the manufacture of the film, it is preferred to make the decomposition of PET as difficult as possible. For example, it can be mentioned that: reducing the water content of PET used as a raw material, reducing the resin temperature during melt mixing, shortening the time for the resin to become a molten state, etc., as described below.

[0075] The lower limit of the water content of the original PET and recycled PET used as raw materials in the film manufacturing is preferably 1 mass ppm, more preferably 5 mass ppm, and further preferably 10 mass ppm. The upper limit of the water content in the film manufacturing is preferably 150 mass ppm, more preferably 100 mass ppm, further preferably 70 mass ppm, particularly preferably 50 mass ppm, and most preferably 30 mass ppm. By setting it below the above, the decomposition of the resin in the film manufacturing process can be suppressed, and the degradation of the recycled resin can be suppressed.

[0076] Regarding the lower limit of the melting temperature of the resin during film manufacturing, in terms of the highest temperature, it is preferably 270°C, more preferably 275°C. By setting it above or above, productivity can be improved. The upper limit of the melting temperature is preferably 290°C, more preferably 288°C, further preferably 286°C, and particularly preferably 285°C. By setting it below the above, the decomposition of the resin in the film manufacturing process can be suppressed, and the deterioration of the recycled resin can be suppressed. It should be noted that, usually, when the film is manufactured, the temperature of the resin is the highest in the second half of the extruder, which can be detected by the value of the thermometer equipped on the extruder.

[0077] The lower limit of the melting time of the resin during film manufacturing is preferably 2 minutes, more preferably 3 minutes. The upper limit of the melting time of the resin during film manufacturing is preferably 20 minutes, more preferably 15 minutes, further preferably minutes, particularly preferably minutes, and most preferably minutes. By setting it to the above or below, the degradation of the recycled resin can be suppressed.

[0078] Furthermore, in the step of pelletizing the recovered PET, it is also important to suppress the decomposition of PET.

[0079] The lower limit of the water content when the recycled PET is pelletized is preferably 1 mass ppm, more preferably 5 mass ppm, and further preferably 10 mass ppm. The upper limit of the water content when the recycled PET is pelletized is preferably 150 mass ppm, more preferably 100 mass ppm, further preferably 70 mass ppm, particularly preferably 50 mass ppm, and most preferably 30 mass ppm. By setting it below the above, the deterioration of the recycled PET can be suppressed.

[0080] Furthermore, when the ear portion (edge) of the recovered PET is used in the film production, it is also preferred to pelletize the PET immediately after cutting off the ear portion.

[0081] Regarding the lower limit of the melting temperature when the recycled PET is pelletized, it is preferably 270°C, more preferably 275°C, with respect to the temperature at the highest point. By setting it above or above, productivity can be improved. The upper limit of the melting temperature when the recycled PET is pelletized is preferably 290°C, more preferably 288°C, further preferably 286°C, and particularly preferably 285°C. By setting it below or above, the deterioration of the recycled resin can be suppressed. It should be noted that, generally, the temperature of the resin is highest in the second half of the extruder, which can be detected by the value of a thermometer equipped on the extruder.

[0082] The lower limit of the melting time when recycling PET granulation is preferably 1 minute, more preferably 2 minutes. The upper limit of the melting time when recycling PET granulation is preferably 15 minutes, more preferably 10 minutes. By setting it below the above, the degradation of the recycled resin can be suppressed.

[0083] When the recycled PET is pelletized, it is preferred to use an extruder equipped with a vent and perform melt kneading while reducing the pressure.

[0084] It should be noted that the reduced molecular weight can also be increased by solid phase polymerization of recycled PET, but except for the purpose of obtaining a film with high IV, low AV, and low CT that cannot be obtained by melt-polymerized PET, solid phase polymerization of recycled PET is not necessarily preferred from an economic point of view.

[0085] In the manufacture of the film, preferably, the molten resin is extruded into a sheet, and after cooling, the obtained unstretched sheet is stretched in at least one direction. In the stretching, when the film is stretched in the longitudinal direction, a roller stretching method is preferably used, and when the film is stretched in the transverse direction, a tenter stretching method is preferably used. In addition, a tenter can also be used to perform simultaneous biaxial stretching in the longitudinal and transverse directions.

[0086] The stretching temperature is preferably 80 to 130° C., more preferably 85 to 120° C., in both the longitudinal and transverse directions. The temperature can be adjusted within this range according to the required properties.

[0087] The stretching ratio is preferably 3 to 8 times, more preferably 3.3 to 7 times, in at least one of the longitudinal and transverse directions, which are the main stretching directions. The stretching ratio of the other direction can also be adjusted according to the properties required for the film to be manufactured.

[0088] The lower limit of the IV of the film is preferably 0.52 dL / g, more preferably 0.54 dL / g, further preferably 0.55 dL / g, and particularly preferably 0.56 dL / g. The upper limit of the IV of the film is preferably 0.73 dL / g, more preferably 0.70 dL / g, further preferably 0.67 dL / g, particularly preferably 0.65 dL / g, and most preferably 0.63 dL / g. By setting it within the above range, the mechanical properties can be improved, the film forming properties can also be improved, and the decomposition of the recycled PET can be suppressed.

[0089] The lower limit of the AV of the film is preferably 5 eq / ton, more preferably 10 eq / ton. The upper limit of the AV of the film is preferably 80 eq / ton, more preferably 75 eq / ton, further preferably 70 eq / ton, particularly preferably 65 eq / ton, and most preferably 60 eq / ton. By setting it below the above, the decomposition of the recycled PET can be suppressed.

[0090] The lower limit of the CT amount of the film is preferably 0.5% by mass, more preferably 0.7% by mass, and still more preferably 0.8% by mass. The upper limit of the CT amount of the film is preferably 1.1% by mass, and more preferably 1.05% by mass.

[0091] The film may contain a colorant, lubricant particles, an ultraviolet absorber, a melt resistivity adjuster, an antistatic agent, an antioxidant, a heat stabilizer, and the like.

[0092] The film may be a single-layer structure or a multi-layer structure obtained by coextrusion. In the case of a multi-layer structure, the layers may have different compositions, such as adding an ultraviolet absorber only to the middle layer, adding a lubricant only to the surface layer, etc. In addition, the IV, AV, and CT amounts may be different in each layer. In the case of a multi-layer structure, the IV, AV, and CT amounts of the film are values ​​measured as a whole film without separating the layers.

[0093] The polyester film is preferably subjected to a surface treatment in order to improve the adhesion between the polyester film and an adhesive, a coating material, an ink, etc. Examples of the surface treatment include a corona treatment, a plasma treatment, and a flame treatment.

[0094] The polyester film may be provided with an easy-adhesion layer.

[0095] About the resin used in the easy bonding layer, polyester resin, polyurethane resin, polycarbonate resin, acrylic resin etc. can be used, preferably polyester resin, polyester polyurethane resin, polycarbonate polyurethane resin, acrylic resin.The easy bonding layer is preferably cross-linked.As a cross-linking agent, isocyanate compounds, melamine compounds, epoxy resins, oxazoline compounds etc. can be cited.In addition, in order to improve the adhesion with polarizer, adding water-soluble resins such as polyvinyl alcohol is also a useful means.

[0096] The easy-adhesion layer can be formed by coating a polyester film with a water-based coating material to which these resins and, if necessary, a crosslinking agent, particles, etc. are added and then drying the coating material. Examples of the particles include those used for the above-mentioned substrates.

[0097] The easy-adhesive layer can be provided on the stretched film in an offline manner, but is preferably provided in an online manner in the film-making process. When provided in an online manner, it can be any one of before longitudinal stretching and before transverse stretching, but it is preferably applied before transverse stretching, and dried and cross-linked in the preheating, heating, and heat treatment processes of the tenter. It should be noted that in the case of online coating before longitudinal stretching performed by a roller, preferably, after coating, it is dried with a vertical dryer and then guided to the stretching roller.

[0098] The coating amount of the adhesive layer is preferably 0.01 to 1.0 g / m 2 , more preferably 0.03 to 0.5 g / m 2 .

[0099] Polyester films can be used for various purposes as shown below. · Process release film: for example, ceramic green sheet, resin solution film, etc. · Transfer film: for example, metal foil, printed pattern layer, liquid crystal compound phase difference layer, liquid crystal compound polarizer, etc.

[0100] In the release film or the transfer film, a release layer of a fluorine-based resin, a silicone-based resin, an acrylic containing a long-chain alkyl group, a polyolefin, or the like may be provided. Protective film: For example, polarizing plate protective film, surface protective film of image display devices, rear protective film, solar cell back sheet, etc.

[0101] In these applications, an adhesive layer may be provided. On the protective film, an adhesive layer such as a rubber-based, acrylic-based, silicone-based, or urethane-based adhesive layer may be provided. In addition, in the case of a permanent protective film such as a solar cell back sheet, the protective film may be attached to an object by an adhesive. Optical films: for example, lens sheet substrates, prism sheet substrates, nanoimprint film substrates, diffusion sheet substrates, anti-scattering films, polarizer protective films, transparent conductive film substrates, etc.

[0102] In the case of a lens or prism sheet or nanoimprinting, an acrylic compound layer or the like provided on a polyester film can be brought into contact with a mold and cured to form a pattern.

[0103] In the surface protection film of the image display device, etc., the polarizer protection film, etc., a hard coating layer, an anti-reflection layer, an anti-reflection layer, an anti-glare layer, etc. can be provided. In the transparent conductive film, a hard coating layer, a refractive index adjustment layer, etc. can be provided. As the conductive layer of the transparent conductive film, an ITO film, a mesh of metal etching or conductive paste, a coating layer of metal whiskers, etc. can be cited. Films for electrical, electronic and communication use: for example, flexible circuit substrates, cover films, carrier tape covers, electronic tag substrates, IC cards, motor insulation films, etc. Printing substrate film: for example, electronic product labels, advertising labels, event labels, etc. Barrier film: metal vapor-deposited film, metal oxide vapor-deposited film, barrier coating film, etc.

[0104] As metal vapor deposition, aluminum can be mentioned; as metal oxides, aluminum oxide, silicon dioxide, aluminum oxide-silicon composite oxide, etc. can be mentioned; as barrier coatings, sol-gel coatings, coatings containing inorganic layered compound particles, polyvinyl alcohol coatings, ethylene-vinyl alcohol copolymer coatings, vinyl chloride coatings, etc. can be mentioned. ·Laminated films for packaging: lamination with nylon film, polypropylene film, etc. Heat-sealable film: laminated with heat-sealable layers such as polyethylene, polypropylene, copolyester, etc.

[0105] In these laminations, adhesives such as isocyanate-curing type, epoxy-curing type, and radiation-curing type can be used. Heat-shrinkable polyester film: beverage bottle labels, beverage can labels, cap seals, packaging of containers with lids, bundled packaging, etc.

[0106] In these applications, in order to adjust the heat shrinkage characteristics, it is preferred to blend other polyesters or copolyester resins to form a film. Examples of other polyesters include tetramethylene terephthalate and trimethylene terephthalate, and examples of copolyesters include ethylene terephthalate-ethylene isophthalate copolymers, ethylene terephthalate-butylene terephthalate copolymers, ethylene terephthalate-2,2-dimethylpropylene terephthalate copolymers (those obtained by adding neopentyl glycol to a glycol component), ethylene-2,2'-oxydiethylene copolymers (those obtained by adding diethylene glycol to a glycol component), ethylene terephthalate-1,4-cyclohexanedimethylene terephthalate copolymers (those obtained by adding 1,4-cyclohexanedimethanol to a glycol component), and those obtained by copolymerizing these with other components. When all the acidic components and all the diol components in the film are respectively set to 100 mol%, the copolymerization amount and the blending amount can be determined by making the total amount of the copolymer components other than the terephthalic acid component and the ethylene glycol component preferably 5 to 70 mol%, more preferably 8 to 50 mol%, and further preferably 10 to 40 mol%.

[0107] Regarding the polyester film, the polyester resin can be blended with an incompatible resin such as polypropylene, polymethylpentene, polystyrene, etc. and stretched to form a film containing voids. In this case, the incompatible resin is preferably 3 to 30% by mass, more preferably 5 to 20% by mass, relative to the total amount of resin constituting the film.

[0108] In addition, various pigments such as titanium oxide, barium sulfate, and carbon can be added to produce white, black, or other colored films. These films are preferably used for labels, printing films that replace paper, light reflective films, circuit substrates, cards, labels, and the like.

[0109] In addition, polyimide, polyamide-imide, polyamide, polyphenylene sulfide, polyphenylene sulfone, polyphenylene ether, etc. can be added to form a modified polyester film. In this case, the modified resin other than the polyester is preferably 0.5 to 20% by mass, more preferably 1 to 15% by mass, and further preferably 2 to 10% by mass relative to the total amount of resin constituting the film. Example

[0110] Hereinafter, the present invention will be described by way of examples, but the present invention is of course not limited to these examples. (1) Intrinsic viscosity (IV) About 3 g of the sample was freeze-pulverized, dried at 140°C for 15 minutes, and then 0.20 g was weighed and stirred at 100°C for 60 minutes with 20 ml of a mixed solvent of 1,1,2,2-tetrachloroethane and p-chlorophenol mixed at a mass ratio of 1:3 to completely dissolve. After cooling to room temperature, the mixture was filtered through a glass filter to prepare a sample. The dripping time of the sample and the solvent was measured using an Ubbelohde viscometer (manufactured by RIGO Co., Ltd.) adjusted to 30°C, and the intrinsic viscosity [η] was calculated by the following formula.

[0111] [η]=(-1+√(1+4K'ηSp)) / 2K'C ηSp=(τ-τ0)τ0 in, [η]: Intrinsic viscosity (dl / g) ηSp: Specific viscosity (-) K': Huggins constant (= 0.33) C: concentration (=1g / dl) τ: Dropping time of the sample (seconds) τ0: solvent dripping time (seconds)

[0112] (2) Content of specified metal elements in the sample The polyester resin was weighed in a platinum crucible, carbonized in an electric furnace, and then ashed in a muffle furnace at 550°C for 8 hours. The ashed sample was dissolved in 1.2M hydrochloric acid to prepare a sample solution. The prepared sample solution was measured under the following conditions, and the concentrations of antimony and aluminum in the polyester resin were determined by high-frequency inductively coupled plasma emission spectrometry.

[0113] Device: CIROS-120 manufactured by SPECTRO Plasma power: 1400W Plasma gas: 13.0L / min Auxiliary gas: 2.0L / min Atomizer: Cross flow nebulizer Chamber: Cyclone chamber Measurement wavelength: 167.078nm

[0114] (3) Phosphorus content in polyester resin The polyester resin was wet decomposed with sulfuric acid, nitric acid, and perchloric acid, and then neutralized with ammonia water. After adding ammonium molybdate and hydrazine sulfate to the adjusted solution, the absorbance at a wavelength of 830 nm was measured using an ultraviolet-visible spectrophotometer (manufactured by Shimadzu Corporation, UV-1700). The concentration of phosphorus in the polyester resin was determined from a pre-prepared standard curve.

[0115] (4) Acid value The film and the raw material polyester resin were measured by the following method. Sample preparation The film or raw polyester resin is crushed, vacuum dried at 70°C for 24 hours, and then weighed to a range of 0.20±0.0005g using a balance. It should be noted that when measuring the acid value of each layer, a sample of each layer extruded in a single layer is made as a sample. The mass at this time is set to W (g). 10 ml of benzyl alcohol and the weighed sample are added to a test tube, and the test tube is immersed in a benzyl alcohol bath heated to 205°C, and the sample is dissolved while stirring with a glass rod. The samples with a dissolution time of 3 minutes, 5 minutes, and 7 minutes are set to A, B, and C, respectively. Next, prepare a new test tube, add only benzyl alcohol, and treat in the same order, and set the samples with a dissolution time of 3 minutes, 5 minutes, and 7 minutes to a, b, and c, respectively.

[0116] Titration Titrate with a 0.04 mol / l potassium hydroxide solution (ethanol solution) with a known factor. Use phenol red as the indicator, set the time point when the yellow-green color changes to light red as the end point, and calculate the titration amount (ml) of the potassium hydroxide solution. Set the titration amount of samples A, B, and C as XA, XB, and XC (ml). Set the titration amount of samples a, b, and c as Xa, Xb, and Xc (ml).

[0117] Using the titration amounts XA, XB, and XC for each dissolution time, the titration amount V (ml) at the dissolution time of 0 minutes is calculated by the least square method. Similarly, using Xa, Xb, and Xc, the titration amount V0 (ml) is calculated. Next, the acid value is calculated according to the following formula. Carboxyl terminal concentration (eq / ton) = [(V-V0) × 0.04 × NF × 1000] / W NF: Factor of 0.04 mol / l potassium hydroxide solution

[0118] (5) Quantification of cyclic trimers The sample is freeze-crushed or fragmented, and 100 mg of the sample is accurately weighed. Dissolve it in 3 mL of a hexafluoroisopropanol / chloroform mixture (volume ratio = 2 / 3), and further add 20 mL of chloroform to dilute it. Add 10 mL of methanol to precipitate the polymer, and then filter it. Evaporate the filtrate to dryness and use 10 mL of dimethylformamide to make the volume constant. Then, the amount of cyclic trimer in the polyester resin or in the hollow molded body is quantified by the following high performance liquid chromatography. Repeat the above operation 5 times, and the average value is taken as the CT content.

[0119] Device: L-7000 (manufactured by Hitachi, Ltd.) Chromatographic column: μ-Bondasphere C18 5μ100 angstroms 3.9 mm×15 cm (manufactured by Waters) Solvent: Eluent A: 2% acetic acid / water (v / v) Eluent B: acetonitrile Gradient B%: 10→100% (0→55 min) Flow rate: 0.8 mL / min Temperature: 30℃ Detector: UV-259nm

[0120] (6) Elongation at break (TE) The test was carried out according to JIS-C-2318-1997 5.3.31 (tensile strength and elongation). Film test pieces with a width of 10 mm and a length of 190 mm were sampled from the MD direction (longitudinal direction, film winding direction) and the TD direction (transverse direction, direction perpendicular to the MD direction). The film test piece was placed on a tensile testing machine (Tensilon RTC-125A manufactured by ORIENTEC), and stretched at a distance of 100 mm between the clamps and a pulling speed of 200 mm / min at a temperature of 23°C and a humidity of 65% RH. The stress required for breaking and the elongation of the film were measured to determine the breaking elongation (%).

[0121] The reduction rate of elongation at break is a value obtained by dividing the measured value by the elongation at break of a film produced only from the original PET of the reference example.

[0122] Preparation of PET resin Chemically recycled PET (A1, A2) It is obtained by polycondensing chemically recycled BHET obtained by depolymerizing recycled PET bottles, PET fibers, etc. in the presence of ethylene glycol using a composite catalyst of basic aluminum acetate and Irganox 1222 (manufactured by BASF). The properties are shown in Table 2.

[0123] The total amount of the acid value and the hydroxyl value of the chemically recycled BHET used was 8100 eq / ton. The measurement was performed according to the following method. (Determination of BHET Acid Value (AV)) Accurately weigh 1.00g of the sample crushed with a hand-held grinder (crusher), and add 20ml of pyridine. Add a few zeolites and boil and reflux for 15 minutes to dissolve them. After boiling and reflux, immediately add 10ml of pure water and cool to room temperature. Use phenolphthalein as an indicator and titrate with N / 10-NaOH. The same operation is performed for a blank test without adding a sample. It should be noted that when the oligomer is insoluble in pyridine, it is carried out in benzyl alcohol. Calculate AV (eq / ton) according to the following formula.

[0124] AV=(AB)×0.1×f×1000 / W (A = titration number (ml), B = titration number of blank test (ml), f = N / 10-NaOH factor, W = weight of sample (g)

[0125] (Determination of Hydroxyl Value (OHV)) Accurately weigh 0.50g of the sample crushed with a hand-held grinder (crusher), add 10ml of acetylating agent (0.5mol / L acetic anhydride pyridine solution), and immerse in a water tank above 95°C for 90 minutes. After taking it out of the water tank, immediately add 10ml of pure water and cool it to room temperature. Use phenolphthalein as an indicator and use N / 5-NaOH-CH3OH solution for titration. The same operation is performed for a blank test without adding a sample. It should be noted that phenolphthalein is used as an indicator in advance, and 20ml of N / 10-hydrochloric acid is titrated with N / 5-NaOH-CH3OH solution, and the factor (F) of the solution is calculated in advance according to the following formula.

[0126] F=0.1×f×20 / a (f = N / 10-hydrochloric acid factor, a = titration number (ml)) Calculate OHV (eq / ton) according to the following formula.

[0127] OHVo={(BA)×F×1000 / W}+AV (A = titration number (ml), B = titration number of blank test (ml), F = N / 5-NaOH-CH3OH solution factor, W = weight of sample (g)

[0128] Chemically recycled PET (A3, A4) It is obtained by polycondensation using chemically recycled BHET used in A1 with an antimony trioxide catalyst. The properties are shown in Table 2.

[0129] Non-chemically recycled PET (B1) The IV of the product obtained by polycondensation of terephthalic acid and ethylene glycol using an antimony trioxide catalyst was 0.62 dL / g, the AV was 34 eq / ton, and the CT content was 0.92 mass %. The properties are shown in Table 2.

[0130] [Table 2] PET resin A1 A2 A3 A4 B1 Chemically recycled BHET amount (mass %) 100 100 100 100 0 catalyst Al / P Al / P Sb Sb Sb Amount of Al in resin (ppm by mass) 16 21 - - - P content in resin (ppm by mass) 25 45 - - - Sb content in resin (ppm by mass) - - 155 350 125 IV (dL / g) 0.617 0.668 0.624 0.611 0.62 AV(eq / ton) 32 30 30 32 3.4 CT amount (mass %) 0.92 0.92 0.92 0.92 0.92

[0131] Production of recycled PET pellets The dried raw pellets were charged into the film production equipment used in the examples, extruded into a sheet using a cooling roll die under the conditions described in Table 2, and then wound into a roll without stretching.

[0132] The sheet wound into a roll is crushed by a crusher, placed in a flexible container bag, and placed in a room without air conditioning for more than one week. Then, the crushed resin is dried under reduced pressure and put into a twin-screw mixer, melted and extruded into strands under the conditions described in Table 2, and then fragmented after being cooled with water to obtain pellets of recycled resin. It should be noted that the melting time in Table 2 refers to the average time from the area set above the melting point of the film to the outlet of the die in the extruder, and is the value obtained by dividing the total amount of resin in the extruder obtained by simulation and from the piping to the outlet of the die by the volume of the resin put in per unit time.

[0133] The properties of the recovered resin are shown in Table 3.

[0134] [Table 3]

[0135] Membrane manufacturing The virgin PET pellets and the recycled PET pellets were mixed, dried under reduced pressure, and then put into the feed hopper of the film manufacturing equipment and extruded into a sheet on a cooling roll under the conditions described in Table 3. The obtained sheet was stretched to 3.4 times in the longitudinal direction at 90°C using rolls with different circumferences. Then, it was stretched to 3.8 times in the width direction in a tenter heated to 120°C, and then heat-set at 230°C to obtain a biaxially stretched polyester film with a thickness of 40 μm.

[0136] Each reference example was manufactured using only virgin resin.

[0137] In the examples, even if the amount of recycled resin increases, the difference in IV and AV of the membrane is small compared to the reference example, and the decrease in physical properties (breaking strength) is also small. In particular, in Examples 1 to 6 using Al-based catalysts, the difference in IV, AV, and membrane physical properties is small, and there is almost no concern that problems will occur even when the amount of recycled resin input changes significantly.

[0138] On the other hand, in the comparative examples, in Comparative Example 1 using 10% by mass of recycled resin, the difference in IV and AV of the film was small compared to the reference example, and there was no decrease in physical properties (breaking strength), but when the recycled resin was set to 35%, a decrease in IV, an increase in AV, and a decrease in physical properties were observed. In order to manufacture films with the same characteristics, the input amount of recycled resin is limited. Furthermore, if the input amount of recycled resin increases, there is a possibility that the film is easily further deteriorated when exposed to a humid and hot state for a long time, and it is also difficult to obtain a stable quality film from the perspective of durability.

[0139] [Table 4] [Industrial Applicability]

[0140] According to the present invention, a polyester film can be obtained, in which the various properties of the obtained film do not change significantly even if the amount of recycled polyester film added fluctuates in the film made of chemically recycled polyethylene terephthalate. This makes it possible to provide a film with a high effect of reducing environmental load, and as a film with stable quality even if the production volume fluctuates, it makes a great contribution to the industry.

Claims

1. A polyester film comprising a chemically recycled polyethylene terephthalate resin obtained by polycondensing a raw material containing bis(2-hydroxyethyl)terephthalate obtained by decomposing a polyester resin using an aluminum compound and a phosphorus compound as a catalyst.

2. The polyester film according to claim 1, wherein The ratio of the raw material containing bis(2-hydroxyethyl) terephthalate is 50% by mass or more.

3. The polyester film according to claim 1 or 2, wherein The polyester resin includes a recycled polyester resin obtained from a film production process.

4. The polyester film according to claim 3, wherein The ratio of the recovered polyester resin is 5 to 50% by mass in the entire polyester resin constituting the polyester film.

5. The polyester film according to claim 1 or 3, wherein The intrinsic viscosity of the polyester resin constituting the polyester film is 0.52 to 0.73 dL / g.

6. The polyester film according to claim 1 or 3, wherein The acid value of the polyester resin constituting the polyester film is 5 to 80 dL / g.

7. A method for producing a polyester film, characterized in that: The invention comprises the following steps: producing a polyester film using a chemically recycled polyethylene terephthalate resin obtained by polycondensing a raw material containing bis(2-hydroxyethyl) terephthalate obtained by decomposing a polyester resin; Unused chemically recycled polyethylene terephthalate resin obtained by polycondensing the raw material containing bis(2-hydroxyethyl) terephthalate and polyethylene terephthalate resin obtained by recovering a melt-formed product discharged from the step of manufacturing the polyester film are melt-mixed and formed into a film.

8. The method for producing a polyester film according to claim 7, wherein: The recycled polyethylene terephthalate resin is 5 to 50% by mass based on the total amount of the unused chemically recycled polyethylene terephthalate resin and the recycled polyethylene terephthalate resin.

9. The method for producing a polyester film according to claim 7 or 8, wherein: In the chemically recycled polyethylene terephthalate resin obtained by polycondensing the raw material containing bis(2-hydroxyethyl) terephthalate, the proportion of bis(2-hydroxyethyl) terephthalate obtained by decomposing a polyester resin is 50% by mass or more relative to the total amount of bis(2-hydroxyethyl) terephthalate used as a raw material for the polycondensation resin.

10. The method for producing a polyester film according to claim 7 or 8, wherein: The chemically recycled polyethylene terephthalate resin obtained by polycondensing bis(2-hydroxyethyl)terephthalate obtained by decomposing the polyester resin contains an aluminum compound and a phosphorus compound as a catalyst.

11. The method for producing a polyester film according to claim 7 or 8, wherein: The difference between the intrinsic viscosity of the unused chemically recycled polyethylene terephthalate resin and the intrinsic viscosity of the recycled polyethylene terephthalate resin is 0.1 dL / g or less.

12. The method for producing a polyester film according to claim 7 or 8, wherein: The ratio of the intrinsic viscosity of the unused chemically recycled polyethylene terephthalate resin to the intrinsic viscosity of the recycled polyethylene terephthalate resin is 0.85-1.

13. The method for producing a polyester film according to claim 7 or 8, wherein: The difference between the acid value of the unused chemically recycled polyethylene terephthalate resin and the acid value of the recovered polyethylene terephthalate resin is 22 eq / ton or less.

Citation Information

Patent Citations

  • Method for producing polyester film

    JP2004175912A